2011
DOI: 10.1002/jtr.1863
|View full text |Cite
|
Sign up to set email alerts
|

Factors that Affect the Levels of Tourists' Satisfaction and Loyalty towards Food Festivals: a Case Study of Macau

Abstract: The present study investigates the factors that affect tourists' satisfaction towards food festivals and explores whether tourists intend to revisit and/or recommend food festivals to others. Based on personal interviews with 40 study subjects, eight factors that affect their satisfaction levels were identified: location and accessibility, food, venue facility, environment/ambiance, service, entertainment, timing and festival size. The majority of tourists were satisfied with the Macau Food Festival and intend… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
102
2
18

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 119 publications
(136 citation statements)
references
References 33 publications
14
102
2
18
Order By: Relevance
“…Innovative possibilities to develop the new concept of health and wellness to diversify festivals into a distinctive market product or as an important aspect of existing festivals exist (Mason & Paggiaro, 2012;Voigt, Brown, & Howat, 2011). Festivals are events and social phenomena encountered in virtually all human cultures, and function as cultural resources for an area that wishes to host visitors (Delbosc, 2008;Getz, 2008;Wan & Chan, 2013). Moreover, festivals attract attendance for the purpose of socialization, community celebration and enjoyment (Arcodia & Whitford, 2006;Lee & Arcodia, 2011;Nicholson & Pearce, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Innovative possibilities to develop the new concept of health and wellness to diversify festivals into a distinctive market product or as an important aspect of existing festivals exist (Mason & Paggiaro, 2012;Voigt, Brown, & Howat, 2011). Festivals are events and social phenomena encountered in virtually all human cultures, and function as cultural resources for an area that wishes to host visitors (Delbosc, 2008;Getz, 2008;Wan & Chan, 2013). Moreover, festivals attract attendance for the purpose of socialization, community celebration and enjoyment (Arcodia & Whitford, 2006;Lee & Arcodia, 2011;Nicholson & Pearce, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Place attachment broadly refers to the idea that people are "attached" to places if they share an emotional tie and if they associate place-related meaning from social interactions occurring within the place (Milligan, 1998 safety/security, socialization, and entertainment. Wan and Chan (2013) found that eight festival dimensions (location and accessibility, food, venue facility, environment/ambiance, service, entertainment, timing and festival size) affected customer satisfaction, revisit behavior, and word of mouth regarding the Macau Food Festival. Therefore, context is essential to determine the dimensions of a festivalscape.…”
Section: Place Attachmentmentioning
confidence: 99%
“…El turismo gastronómico es abordado por la literatura científica en diferentes partes del mundo, destacando, sobre todo, el continente asiático (Wan & Chan, 2013), ya que es precisamente este continente, y debido sobre todo a la diferente concepción que existe con la cocina occidental, el que está marcando la tendencia en este segmento, sin olvidar a Europa (Tikkanen, 2007;López-Guzmán & Sánchez-Cañizares, 2012;Gagić, Tešanović, Ivkov-Džigurski, Pivac & Jovičić, 2013) y Estados Unidos (Smith & Costello, 2009). Sin embargo, son aún escasos los trabajos que estudian la relación entre el turismo y la gastronomía en América Latina.…”
Section: Revisión De La Literaturaunclassified